Penanganan Dampak Negatif Teknologi dalam Pembelajaran di Sekolah - Muhammad Akbar Jibran; Anita Puji Astutik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The advancement of digital technology has brought significant impacts in the world of education, both on the positive and negative sides. This study aims to identify and address the negative impact of the use of digital technology in the learning process, especially at SMA Muhammadiyah 10 Gresik. The research method used is descriptive qualitative with observation techniques and interviews with teachers and students. The results show that although technology facilitates access to information and improves learning efficiency, its uncontrolled use can cause distraction, decreased learning focus, and moral and social disruption of learners. In addition, unwise use of the internet can also lead to addiction, cyberbullying and misuse of information. To overcome this, collaboration between teachers, schools and parents is needed to build character, organize appropriate learning strategies, and provide controls and facilities that support the positive use of technology. Cultivating digital ethics and technology literacy are key to creating a healthy and responsible learning environment in the digital era.